INFLUENCE OF LEXICAL AND SUBLEXICAL IN ADULTS ILLITERATES - Carpio Fernández, María Villa; Justicia Justicia, Fernando (Anales de Psicología / Annals of Psychology, 2000)
The main aim of our study was to find out the effect of several lexical and sublexical variables (word length, lexical frequency, lexical category and grammatical category) in the acquisition of reading in adult illiterates in a transparent language such as Spanish. The second goal of our study was the comparison of the effect of these variablse. Forty four people illiterate between the ages 42 and 72 years, were tested. None of the subjects had attended school in chidlhood. However, twenty two had attended literacy classes for a period bellond to three years. All the illiterate subjects were assessed using a reading test composed of 306 items in which we balanced all the variables. The dependent variable was the percentage of correct response in a descontextualized word reading test. Our results showed that all the above mentioned variables produced a significant effect on the number of errors made by the adults. The four variables studied showed the same effect on reading performance for both two group, indicating that the group with less experience reader also use both the lexical and the phonological route. Our data suggest the universality of the dual route mode.